Exploring Students' Perceptions on Character Education in EFL Classrooms - Annisa Khairir (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2024)
One of the most important areas of character education is exploring students’ perceptions on it. Since students are the target of teaching and learning process, including in learning English subject, examined their perceptions on character education in English language teaching is interesting. This research study reported on a qualitative interview study that exploring how students define, interpret, and reflect the character values in their academic and social live. The participants were students from senior high school, Islamic senior high school, and vocational high school which hold different worldviews and informative perspectives. The instrument for this study was adopted from Suzanne S. Hudd (2010) about perception on character education. The findings show there are the various point of views of character education according to participants’ experience and school background. Additionally, the participants presume character education values which embedded in English lesson have a positive impact.